2021
DOI: 10.3389/fmicb.2021.780458
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabarcoding and Culturomic-Based Microbiome Profiling of Rice Phyllosphere Reveal Diverse and Functional Bacterial Communities for Blast Disease Suppression

Abstract: Phyllosphere—the harsh foliar plant part exposed to vagaries of environmental and climatic variables is a unique habitat for microbial communities. In the present work, we profiled the phyllosphere microbiome of the rice plants using 16S rRNA gene amplicon sequencing (hereafter termed metabarcoding) and the conventional microbiological methods (culturomics) to decipher the microbiome assemblage, composition, and their functions such as antibiosis and defense induction against rice blast disease. The blast susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 85 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…The endophytic M. testaceum isolated from rice leaf was found clustered with a potato leaf endophytic M. testaceum StLB037 ( Morohoshi et al, 2009 ). Before the present study, M. testaceum was reported in diverse habitats like water ( Epova et al, 2022 ), soil ( Yang et al, 2014 ), tannery effluents ( Elahi et al, 2019 ), phyllosphere ( Sahu et al, 2021a , b ), plant endosphere ( Kumar et al, 2021b ), and sometimes as an opportunistic pathogen in clinical samples ( Leal et al, 2016 ). We further studied the endophytism of the bacterium in rice plants using gfp-tagged M. testaceum D18::gfp that could be visualized in the root, stem as well as leaf tissues.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The endophytic M. testaceum isolated from rice leaf was found clustered with a potato leaf endophytic M. testaceum StLB037 ( Morohoshi et al, 2009 ). Before the present study, M. testaceum was reported in diverse habitats like water ( Epova et al, 2022 ), soil ( Yang et al, 2014 ), tannery effluents ( Elahi et al, 2019 ), phyllosphere ( Sahu et al, 2021a , b ), plant endosphere ( Kumar et al, 2021b ), and sometimes as an opportunistic pathogen in clinical samples ( Leal et al, 2016 ). We further studied the endophytism of the bacterium in rice plants using gfp-tagged M. testaceum D18::gfp that could be visualized in the root, stem as well as leaf tissues.…”
Section: Discussionmentioning
confidence: 90%
“…Along with Bacillus amyloliquefaciens , Microbacterium reduced Fusarium verticillioides and the mycotoxin fumonisin B1 and B2 in maize grains ( Sartori et al, 2012 ). Before the present study, leaf epiphytic Microbacterium testaceum was reported to elicit defense responses leading to blast disease suppression upon phyllo bacterization of rice cultivar Pusa Basmati-1 ( Sahu et al, 2021b ). However, published literature on the biocontrol potential of M. testaceum against blast disease is scanty.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…To meet future rice production challenges, there is an urgent need to develop strategies acceptable to all rice farming stakeholders. The plant microbiome, the phytobiome, presents a novel opportunity to harness pathogen-competing and crop-cooperating microbiota [ 12 ]. Rice is a tropical plant colonized by diverse microorganisms such as epiphytes and endophytes [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the year 2000 onwards, pearl millet blast disease was observed widespread across India [ 8 , 14 ]. Therefore, to prevent inadvertent dissemination and minimize the losses, the deployment of blast-resistant genes and the application of agrochemicals are widely practiced [ 8 , 14 , 15 , 16 ]. However, these strategies appear inadequate in blast-endemic areas because of variable host resistance, the emergence of new pathotypes, and the toxic nature of fungicides.…”
Section: Introductionmentioning
confidence: 99%